1999
DOI: 10.1159/000012032
|View full text |Cite
|
Sign up to set email alerts
|

An Early Phase II Study of Oral S-1, a Newly Developed 5-Fluorouracil Derivative for Advanced and Recurrent Gastrointestinal Cancers

Abstract: 5-Fluorouracil (5-FU) or a 5-FU derivative 1-(2-tetrahydrofuryl)-5-fluorouracil (FT) has been widely prescribed for patients with gastrointestinal cancer. However, the phosphorylation of 5-FU in the digestive tract causes gastrointestinal toxicities. 5-FU is also rapidly degraded to α-fluoro-β-alanine after contact with dihydropyrimidine dehydrogenase (DPDase) which is mainly present in the liver. Therefore, to overcome these metabolic events, S-1, an antitumor agent was developed, based on the biochemical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 18 publications
4
125
1
Order By: Relevance
“…S-1, as a prodrug of 5-FU, has been developed to increase the eYcacy and decrease the gastrointestinal toxicities of 5-FU [4,8]. In several phase II studies, S-1 alone has had modest antitumor activity in advanced gastric cancer [3,11,14,21,22]. A phase III trial of comparing S-1 with 5-FU was reported that of S-1 showed not inferior to 5-FU in overall survival (S-1 vs. 5-FU; 11.4 month vs. 10.8 month) [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…S-1, as a prodrug of 5-FU, has been developed to increase the eYcacy and decrease the gastrointestinal toxicities of 5-FU [4,8]. In several phase II studies, S-1 alone has had modest antitumor activity in advanced gastric cancer [3,11,14,21,22]. A phase III trial of comparing S-1 with 5-FU was reported that of S-1 showed not inferior to 5-FU in overall survival (S-1 vs. 5-FU; 11.4 month vs. 10.8 month) [19].…”
Section: Discussionmentioning
confidence: 99%
“…The response rates with S-1 monotherapy, in patients with advanced gastric cancer, as the Wrst-line therapy were variable, 44-49% in Japan, 16.1% in Korea and 26.1% in Europe [3,11,14,21,22]. The response rates reported from the Japanese trials were higher than those from the Korean and European trials were.…”
Section: Time (Weeks)mentioning
confidence: 97%
See 2 more Smart Citations
“…Phase I and early phase II studies of S-1 as a single agent proposed 80 mg m À2 day À1 given orally for 28 consecutive days, followed by a 2-week rest period, as the tentative recommended dosage (Horikoshi et al, 1996;Sugimachi et al, 1999). A number of studies have reported that S-1 monotherapy is effective against gastric cancer, with response rates ranging from 26 to 53% (Horikoshi et al, 1996;Sakata et al, 1998;Koizumi et al, 2000;Chollet et al, 2003).…”
mentioning
confidence: 99%